2023
DOI: 10.1212/wnl.0000000000207114
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormones and Calcitonin Gene–Related Peptide in Women With Migraine

Abstract: Background and Objectives:Sex hormones may modulate CGRP release in the trigeminovascular system. We studied CGRP concentrations in plasma and tear fluid in female participants with episodic migraine (EM) and a regular menstrual cycle (RMC), female participants with EM and combined oral contraception (COC), and female participants with EM in the postmenopause. For control, we analyzed three corresponding groups of age-matched female participants without EM.Methods:Participants with a RMC had two visits: during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 50 publications
0
29
0
3
Order By: Relevance
“…29 Given the high rate of migraine type HA after TBI, 4,6,30,31 the risk elevation for female individuals could be explained by their known migraine-type HA propensity, 32 with a potential mechanism of unmasking a genetic predisposition 33 and/or hormonally mediated increases in calcitonin gene-related peptide levels. 34 We found that in addition to females, individuals of Black race and lower education level were also at greater risk for chronic HA after moderate to severe TBI. Socioeconomic factors are known to influence outcomes across a broad range of health conditions.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…29 Given the high rate of migraine type HA after TBI, 4,6,30,31 the risk elevation for female individuals could be explained by their known migraine-type HA propensity, 32 with a potential mechanism of unmasking a genetic predisposition 33 and/or hormonally mediated increases in calcitonin gene-related peptide levels. 34 We found that in addition to females, individuals of Black race and lower education level were also at greater risk for chronic HA after moderate to severe TBI. Socioeconomic factors are known to influence outcomes across a broad range of health conditions.…”
Section: Discussionmentioning
confidence: 62%
“…Penetrating-type TBI is also associated with other long-term complications after TBI, including seizures and poorer overall functional status 29. Given the high rate of migraine type HA after TBI,4,6,30,31 the risk elevation for female individuals could be explained by their known migraine-type HA propensity,32 with a potential mechanism of unmasking a genetic predisposition33 and/or hormonally mediated increases in calcitonin gene–related peptide levels 34…”
Section: Discussionmentioning
confidence: 99%
“…The fall in serum estradiol levels which occurs in the perimenstrual period is considered a potent and predictable trigger for migraine, possibly triggering migraine by lowering the trigeminal activation threshold 2,5,8,14 . A recent study examined the levels of CGRP in plasma and tear fluid of women over their menstrual cycles, and suggested that women with episodic migraine have hormone‐dependent changes in plasma and tear CGRP levels 22 . These changes in CGRP levels were not seen in women who did not have migraine, or who had episodic migraine and were taking hormonal contraceptives.…”
Section: Discussionmentioning
confidence: 99%
“…Eine Studie der Charité Berlin konnte zeigen, dass die CGRP-Konzentrationen (Plasma und Tränenflüssigkeit) während der Menstruation bei Patientinnen mit Migräne deutlich höher waren als bei gesunden Kontrollprobandinnen. Darüber hinaus waren die CGRP-Konzentrationen während der Menstruation höher als bei Einnahme einer hormonellen Kontrazeption, dies erscheint passend zur genannten Hypothese [26].…”
Section: Migräne Und Hormoneunclassified